2001
DOI: 10.1046/j.1444-2906.2001.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of sediment quality in and around fish cage farms: A case study of aquaculture in the Seto Inland Sea, Japan

Abstract: Fish cage farming generates large amounts of organic waste in the form of unconsumed feed and fecal matter, resulting in sediment deterioration and a threat to its own sustainability. Field studies analysed the scale of the impact of fish cage farming on sediment quality, variability of impact and spread of sediment enrichment in the vicinity of a fish farm. Two fish culture sites near the Fukuyama area of the Seto Inland Sea of Japan were chosen for the study. There was a significant difference between the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…Various studies have reported the development of anoxic conditions in fish farm sediment. Redox potential as low as −200 mV(Eh) has been reported in fish farm sediment 8,9 . Production of toxic gases like methane and H 2 S that adversely affect the benthic organisms has also been reported 2,10 …”
Section: Introductionsupporting
confidence: 93%
“…Various studies have reported the development of anoxic conditions in fish farm sediment. Redox potential as low as −200 mV(Eh) has been reported in fish farm sediment 8,9 . Production of toxic gases like methane and H 2 S that adversely affect the benthic organisms has also been reported 2,10 …”
Section: Introductionsupporting
confidence: 93%
“…According to the law, the total sulfide levels in the bottom sediment measured as AVS-S concentration should be kept under 2.5 mg/g dry mud. For example, in two sea bream fisheries in the Seto Inland Sea, the total sulfide levels were 0.9±0.5 mg/g and 1.2±0.6 mg/g: the control values in two other areas without fisheries were 0.2±0.1 mg/g and 0.3±0.2 mg/g (Pawar et al, 2001). The total sulfide levels in Tsukumo Bay are thus similar to the control levels at appropriate fish farms.…”
Section: Discussionmentioning
confidence: 54%
“…A case study of the sediment quality in and around fish cage farms found a significant difference between the sediment below aquaculture pens and that from non-fish farmed areas. Below cage farms, the sediment was found to be acidic, sulfidic, and extremely reducing (Pawar et al 2001). The accumulation of solid waste from feces and uneaten food has potentially significant effects on the quality of marine habitat available for benthic (bottom-dwelling) animals and wildlife dependent on the benthos.…”
Section: Sedimentation Of Outputsmentioning
confidence: 96%